Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 190715 by sciencestudentW last updated on 09/Apr/23

if (5m−1)x^2 −(5m+2)x+3m−2=0  and  x_1 =x_2   then find  m=?

$${if}\:\left(\mathrm{5}{m}−\mathrm{1}\right){x}^{\mathrm{2}} −\left(\mathrm{5}{m}+\mathrm{2}\right){x}+\mathrm{3}{m}−\mathrm{2}=\mathrm{0} \\ $$$${and}\:\:{x}_{\mathrm{1}} ={x}_{\mathrm{2}} \:\:{then}\:{find}\:\:{m}=? \\ $$

Answered by cortano12 last updated on 10/Apr/23

 ⇒ 25m^2 +20m+4−4(5m−1)(3m−2)=0  ⇒25m^2 +20m+4−4(15m^2 −13m+2)=0  ⇒−35m^2 +72m−4=0  ⇒35m^2 −72m+4=0  ⇒(m−2)(35m−2)=0  ⇒ m=2 or m=(2/(35))

$$\:\Rightarrow\:\mathrm{25m}^{\mathrm{2}} +\mathrm{20m}+\mathrm{4}−\mathrm{4}\left(\mathrm{5m}−\mathrm{1}\right)\left(\mathrm{3m}−\mathrm{2}\right)=\mathrm{0} \\ $$$$\Rightarrow\mathrm{25m}^{\mathrm{2}} +\mathrm{20m}+\mathrm{4}−\mathrm{4}\left(\mathrm{15m}^{\mathrm{2}} −\mathrm{13m}+\mathrm{2}\right)=\mathrm{0} \\ $$$$\Rightarrow−\mathrm{35m}^{\mathrm{2}} +\mathrm{72m}−\mathrm{4}=\mathrm{0} \\ $$$$\Rightarrow\mathrm{35m}^{\mathrm{2}} −\mathrm{72m}+\mathrm{4}=\mathrm{0} \\ $$$$\Rightarrow\left(\mathrm{m}−\mathrm{2}\right)\left(\mathrm{35m}−\mathrm{2}\right)=\mathrm{0} \\ $$$$\Rightarrow\:\mathrm{m}=\mathrm{2}\:\mathrm{or}\:\mathrm{m}=\frac{\mathrm{2}}{\mathrm{35}}\: \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com